using the identity. a square -b square = (a+b) (a-b) find the value. 1, 25a square- 49b square.2, z square- 16. 3, (6x+ 7y) (6y-7y). 4,

Question

using the identity. a square -b square = (a+b) (a-b) find the value. 1, 25a square- 49b square.2, z square- 16. 3, (6x+ 7y) (6y-7y). 4,(4-x) ( 4+x).5,(b+7)(b-7). please give answers​

in progress 0
Hadley 1 week 2021-09-11T05:01:02+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-11T05:02:37+00:00

    Step-by-step explanation:

    1. (5a) {}^{2}  - (7b) { }^{2}  = (5a + 7b)(5a - 7b)
    2. (z) {}^{2}  -( 4) {}^{2}  = (z + 4)(z  - 4)
    3. (6x) {}^{2}  - (7y) {}^{2}  = 36x {}^{2}  - 49y {}^{2}
    4. (4) {}^{2}  - (x) {}^{2}   = 16 - x {}^{2}
    5. (b) {}^{2}  - (7) {}^{2}  = b { }^{ 2}  - 49

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )